Isolated Electron‐Rich Ruthenium Atoms in Intermetallic Compounds for Boosting Electrochemical Nitric Oxide Reduction to Ammonia. (14th December 2022) - Zhang, Huaifang; Li, Yanbo; Cheng, Chuanqi; Zhou, Jin; Yin, Pengfei; Wu, Haoming; Liang, Zhiqin; Zhang, Jiangwei; Yun, Qinbai; Wang, An‐Liang; Zhu, Lijie; Zhang, Bin; et al.
Abstract: The direct electrochemical nitric oxide reduction reaction (NORR) is an attractive technique for converting NO into NH3 with low power consumption under ambient conditions. Optimizing the electronic structure of the active sites can greatly improve the performance of electrocatalysts. Herein, we prepare body‐centered cubic RuGa intermetallic compounds (i.e., bcc RuGa IMCs) via a substrate‐anchored thermal annealing method. The electrocatalyst exhibits a remarkable NH4 + yield rate of 320.6 μmol h −1 mg −1 Ru with the corresponding Faradaic efficiency of 72.3 % at very low potential of −0.2 V vs. reversible hydrogen electrode (RHE) in neutral media. Theoretical calculations reveal that the electron‐rich Ru atoms in bcc RuGa IMCs facilitate the adsorption and activation of *HNO intermediate. Hence, the energy barrier of the potential‐determining step in NORR could be greatly reduced. Abstract : The body‐centered cubic RuGa intermetallic compounds (i.e., bcc RuGa IMCs) are prepared via a substrate‐anchored thermal annealing method. Electron‐rich Ru atoms are the active sites and are isolated in bcc RuGa IMCs, which promote electron transfer from the electrocatalyst to key intermediates, thereby effectively improving the electrocatalytic performance of the nitric oxide reduction reaction (NORR).